Ozone therapy as support in the treatment of diabetic foot ulcer. A case report - Isidro Matos Lamote; Jorge Enrique Rodríguez León; Carlos García Arencibia; Maydelin Pérez Reina (Medisur)
One of the most common complications of diabetes mellitus is diabetic foot ulcer, as an important source of morbidity and mortality. The case of a 43-years-old patient with a diagnosis of type 2 diabetes mellitus, of seven years of evolution, referred from the Emergency Department of the Dr. Mario Muñoz Monroy University Polyclinic, Abreus, with the diagnosis of neuroinfectious diabetic foot complicated with an abscess is presented. Drainage of the abscess, modification of insulin treatment, and debridement of the lesion were performed. In addition, antibiotics and Heberprot-P® were indicated. In the absence of satisfactory evolution, new debridement was performed, with amputation of the third and fourth toes of the left foot; the initial treatment was resumed, this time combined with local and rectal ozone therapy. From week 18 on, the patient progressed favorably, with the presence of good granulation, gradual disappearance of pain and acceleration of the complete healing process of the lesion, in addition to achieving efficient metabolic control. The described case confirms the efficacy and safety of the Heberprot-P® combined use and ozone therapy.